The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1074/jbc.ra120.013897
|View full text |Cite
|
Sign up to set email alerts
|

The insufficiency of ATG4A in macroautophagy

Abstract: During autophagy, LC3 and GABARAP proteins become covalently attached to phosphatidylethanolamine (PE) on the growing autophagosome. This attachment is also reversible. Deconjugation (or delipidation) involves the proteolytic cleavage of an isopeptide bond between LC3 or GABARAP and the PE headgroup. This cleavage is carried about by the ATG4 family of proteases (ATG4A, B, C and D). Many studies have established that ATG4B is the most active of these proteases and is sufficient for autophagy progression in sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…This technique involves several centrifugation steps to separate membrane compartments from one another (Figure 3A). Consistent with Strømhaug et al and our own previous results (Jeong et al, 2009;Nguyen et al, 2020;Strømhaug et al, 1998), GFP-LC3B-II and LC3B-II were strongly enriched in fraction 6 in WT cells (Figure 3, B, D, and G), hereafter referred to as the autophagosome (AP) fraction. Strikingly, ATG9A was also robustly enriched in this fraction (Figure 3, B, D and E).…”
Section: Atg9a and Lc3b Reside In The Same Membrane Fraction After De...supporting
confidence: 92%
“…This technique involves several centrifugation steps to separate membrane compartments from one another (Figure 3A). Consistent with Strømhaug et al and our own previous results (Jeong et al, 2009;Nguyen et al, 2020;Strømhaug et al, 1998), GFP-LC3B-II and LC3B-II were strongly enriched in fraction 6 in WT cells (Figure 3, B, D, and G), hereafter referred to as the autophagosome (AP) fraction. Strikingly, ATG9A was also robustly enriched in this fraction (Figure 3, B, D and E).…”
Section: Atg9a and Lc3b Reside In The Same Membrane Fraction After De...supporting
confidence: 92%
“…Furthermore, we confirmed that the isoform ATG4B is the major cysteine protease priming the LC3B biosensor, and that its knockout results in a complete lack of priming. Additionally, we provided evidence that ATG4A could mildly contribute to the priming of the LC3B biosensor in the absence of ATG4B, corroborating previous findings concerning a functional redundancy among these isoforms [24, 60]. Interestingly, our biosensor provided novel information on the relevance of specific ATG4B residues for its priming activity.…”
Section: Discussionsupporting
confidence: 88%
“…While in yeast there is just one ATG8 protein, in mammals there are multiple ATG8 orthologues: LC3A, LC3B, LC3C, GABARAP, GABARAPL1 and GABARAPL2 [17]. The ATG8 proteins are synthesised as a precursor and the C‐terminal glycine residue is cleaved by ATG4 to produce the mature ATG8‐I, which will be conjugated to PE, forming the lipidated version ATG8‐II on the membranes of autophagosomal structures [18]. The ATG8 acts as a scaffold for the early core autophagy components by binding protein subunits containing the sequence motif called LC3‐interacting region (LIR) [19].…”
Section: Molecular Mechanisms Of the Autophagic Processmentioning
confidence: 99%